Canopy manipulation practices for optimum colour of redglobe (V.Vinifera L.) - Strydom, Janene (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MscAgric (Viticulture and Oenology))--University of Stellenbosch, 2006.